Impact of Emerging Interaction Techniques on Energy Use in the UK Social Housing. Issue 1 (27th March 2018) - Liu, Shuli; Iweka, Obiajulu; Shukla, Ashish; Wernham, Georgina; Hussain, Atif; Day, Rosie; Gaterell, Mark; Petridis, Panagiotis; Van Der Horst, Dan
End use energy efficiency and fuel poverty is one of the major issues in the UK social housing sector. It is estimated that about 10% of English households live in fuel poverty. During 2015 UK greenhouse gas emission final figures show that the net CO2 emission was reduced by 4.1% between 2014 and 2015. This shows that the UK is on course to attain its second carbon budget with annual 2013–2015 emissions that are each below the estimated level for the period. However, the housing sector lags with a 4% increase in emissions over the same period. More work needs to be done in this sector. Householders can adopt more efficient energy use approaches and make better lifestyle choices to save money and have a safer environment. This research addresses government priorities to reduce energy demand, meet CO2 reduction targets, and reduce domestic reliance on fossil fuels, offering protection from price risks and fuel poverty as well as providing more affordable and comfortable domestic environments. The proposed research paper deals with novel interaction methods on energy use in social housing and how the aforesaid issues can be reflected on. A detailed background study on existing interaction methods and ongoing development of a serious game trialled in 19 households has been carried out. It has been noted that displaying real-time utility use and indoor environmental conditions to householders increased awareness and impacted how energy is being consumed. Furthermore, the proposed paper will investigate end use energy profile pattern changes due to novel interaction methods.